Efficiency of cleaning solutions to remove difficult contamination on weathered float glass exposed in an urban environment - Mendoza Carranza, Elena Kristel (2021)
This study investigates the removal of different contaminants on soda-lime float glass weathered artificially and naturally. Organic, inorganic non-metallic, metallic, and saline contaminants were selected to evaluate the degradation of float glass in contact with them. Bird droppings, cement dust, aluminum particles, and sodium chloride were deposited on the glass surface. The four contaminants altered the glass surface to varying degrees. Glass samples were weathered in a climate chamber for one and seven days. Another set of glass samples was exposed outdoors in Ilmenau, Germany, for 50 days (20 days unsheltered and 30 days sheltered). Before and after the weathering, the glass samples were cleaned with three cleaning agents (DI water, citric acid, and a commercial glass cleaner). The chosen cleaning solutions provided different cleaning results for the glass surfaces. Depending on weathering exposure (artificial or natural), contaminants seem to affect glass surfaces differently. During outdoor weathering, deposits adhere differently to the glass surface treated with different cleaning solutions. In addition, the effectiveness of a commercial protective agent is compared with the chosen cleaning agents. Optical microscopy was used to localize weathering products and evaluate glass surface degradation. Energy-dispersive X-ray spectroscopy (EDX) and Auger electron spectroscopy (AES) were used to identify chemically the unremoved weathering products. Surface analysis indicated the presence of chlorides and carbonates on the weathering products and more considerable delamination effects on glass naturally exposed under shelter conditions. It has been evaluated that the cleaning agents have influenced the removal of contaminants and the glass durability differently.